A condition‐based maintenance policy for deteriorating units. An application to the cylinder liners of marine engine. (14th March 2014) - Giorgio, Massimiliano; Guida, Maurizio; Pulcini, Gianpaolo; Finkelstein, Maxim
<x xml:space="preserve">Abstract</x> This paper proposes a condition‐based maintenance policy for deteriorating units, which are to be considered failed when their wear exceeds a critical threshold level, even if this exceeding is not associated to a sudden breakdown of the unit but only to degraded performance. Thus, the failure occurrence can be detected only at periodic inspections. In such a framework, given the unit age and state at inspection, a decision‐making rule is proposed to choose the maintenance action to be taken, in order to extend the used life of the unit without significantly increasing its failure probability, so to reduce the life cycle cost. Both the case when all inspection times are planned and the case when an additional maintenance can be scheduled before the next planned inspection are considered. An application to a real case study referring to the wearing process of cylinder liners of some marine diesel engines is illustrated, with the further aim of highlighting the need to correctly model the degradation process. Copyright © 2014 John Wiley & Sons, Ltd.